Meningkatkan Daya Saing UMKM Dumai Melalui Pemasaran Online - Musdiana, Andi Desy; Aditiya, Variza; Lastri, Novelma; Hartuti, Dwi (Jurnal Administrasi Publik dan Bisnis, 2025)
This study aims to enhance the competitiveness of MSMEs (Micro, Small, and Medium Enterprises) in Dumai through online marketing. With the growing development of technology and the increasing accessibility of the internet, online marketing presents a significant opportunity to expand the market reach of MSMEs. This research employs a qualitative approach using case study methodology, analyzing several MSMEs in Dumai that have utilized online marketing. The results show that the application of online marketing strategies can increase product visibility, expand market reach, and improve sales for MSMEs in Dumai..